Determinants of self-rated health in an Irish deprived suburban population – a cross sectional face-to-face household survey. (December 2016) - Darker, Catherine; Donnelly-Swift, Erica; Whiston, Lucy; Moore, Fintan; Barry, Joe
Abstract Background Self-rated health (SRH) is amongst the most frequently assessed health perceptions in epidemiological research. While there is a growing understanding of the role of SRH, a paradigm model has yet to be widely accepted with recent studies concluding that further work is required in determining whether there are important predictors of SRH yet to be highlighted. The aim of this paper is to determine what health and non-health related factors were associated with SRH in a suburban deprived population in Dublin, Ireland. Methods A cross sectional face-to-face household survey was conducted. Sampling consisted of random cluster sampling in 13 electoral divisions, with a sampling frame of 420 houses. Demographic information relating to the primary carer was collected. Health status of the primary carer was measured through SRH. Household level data included the presence or absence of persons with a chronic disease, persons who smoked, persons with a disability and healthcare utilisation of general practitioner and hospital level services. A logistic regression model was utilised in the analysis whereby the odds of primary carers with poor SRH were compared to the odds of carers with good SRH taking health and non-health related factors into account. Results Of the 420 households invited to participate a total of 343 were interviewed (81.6 % response rate). Nearly half of the primary carers indicated their health as being 'good' (n = 158/342; 46.2 %). Adjusting for the effects of other factors, the odds of primary carers with second level education were increased for having poor SRH in comparison to the odds of those with third level education (OR 3.96, 95 % CI (1.44, 11.63)). The odds of primary carers who were renting from the Council were increased for having poor SRH compared to the odds for those who owned their own property (OR 3.09, 95 % CI (1.31, 7.62)). The odds of primary carers that were unemployed (OR 3.91, 95 % CI 1.56, 10.25)) or retired, ill or unable to work (OR 4.06, 95 % CI (1.49, 11.61)) were higher for having poor SRH than the odds of those in employment. If any resident of the household had a chronic illness then the odds of the primary carer were increased for having poor SRH compared to the odds for a primary carer in a household where no resident had a chronic illness (OR 4.78, 95 % CI (2.09, 11.64)). If any resident of the household used the local hospital, the odds of the primary carer were increased for having poor SRH compared to the odds for the primary carer in a household where no resident used the local hospital (OR 2.01, 95 % CI (1.00, 4.14)). Conclusions SRH is affected by both health and non-health related factors. SRH is an easy to administer question that can identify vulnerable people who are at risk of poor health.